Pengaruh Pendidikan Agama Islam Terhadap Kesadaran Beragama Warga Binaan Pemasyarakatan (WBP) Di Rumah Tahanan Negara Kelas IIB Gresik - Mindarti; Amirudin, noor; Ladamay, Man Arfa' (Jurnal Mahasiswa Pendidikan, 2022)
This research is motivated by the nature of education itself, that all human beings have the right to education. Islamic religious education plays an important role in shaping a person's character, especially his religious awareness. Religious awareness is the most important factor in the formation of one's personality. This research study aims to answer the formulation of the problem, namely as follows: (1) Can Islamic religious education affect the religious awareness of Correctional Inmates (WBP) in Class IIB Gresik State Detention Center? (2) To what extent can Islamic religious education affect the religious awareness of Correctional Inmates (WBP) in Class IIB Gresik State Detention Center? The formulation of the problem was discussed through a quantitative study as a comparison of the value of the influence of Islamic religious education carried out at the Gresik RUTAN. The process of collecting data in this study by means of observation, questionnaires, interviews, and documentation. Then this data was analyzed using simple linear regression analysis. The results of the simple regression analysis show that the value of t count = 10.364 is greater than t table = 1.996. And the value of Sig = 0.000 is smaller than 0.05, so the researcher can conclude that Islamic religious education at the Gresik RUTAN can affect the religious awareness of WBP. While the percentage of the influence is equal to 61.6%.